Usher syndrome Type I in an adult Nepalese male: a rare case report - Sahu, Sabin; Singh, Sanjay Kumar (Nepalese Journal of Ophthalmology, 2018)
Usher syndrome, also known as retinitis pigmentosa-dysacusis syndrome, is an extremely rare genetic disorder, characterized by retinitis pigmentosa (RP) and congenital sensorineural hearing loss. It has been estimated to account for 3-6% of the congenitally deaf population, upto 8-33% of individuals with RP and half of all cases with combined deafness and blindness (Vernon M,1969; Boughman JA et al,1983). The prevalence of Usher syndrome have been reported to range from 3.5 to 6.2 per 100,000 in different populations (Vernon M,1969; Boughman JA et al,1983; Yan D et al, 2010). We report a case of Usher syndrome type I in an adult Nepalese male with typical congenital profound hearing loss, and night blindness secondary to retinitis pigmentosa.